Pertanggungjawaban Direksi Disuatu Perseroan Terbatas Ketika Terjadi Kepailitan Pada Umumnya Dan Menurut Doktrin Hukum Perusahaan & Undang-Undang No.40 Tahun 2007 - M.Faisal Rahendra Lubis (Universitas Islam Sumatera Utara, 2018)
In a company, there is a meeting known as General Meeting of Shareholders (GMS), Board of Directors, and Board of Commissioners. For that, there is a director who is fully responsible for managing a company both inside and outside of the Court based on the provisions of the General Meeting of Shareholders (GMS) and the Board of Commissioners. Business people want more limited liability. It means that there is separation of private property from the limited liability, or the separation of private property from the third parties. Limited Company, hereinafter referred to as the Company, is a legal entity as a capital alliance, established under the agreement, conducting or running the wheel of business activity with a capital base which is entirely divided into shares, and it complies with the requirements of the Law on Limited Liability Companies and the Rules of implementation as well. Important organs within the limited liability company have been regulated in Laws No. 40, 2007 about Limited Liability Company. Each member of the Board of Directors must also have good intentions and full responsibility in carrying out duties for the benefit of the company. If in performing their duties, there is an indication that a director abuses his power for personal gain and causes financial loss resulting in bankruptcy of the company, the director has to be responsible for that or his personal assets will be used as collateral for the repayment of the Company's debts in the condition of bankruptcy. Keywords: Accountability, Board of Directors, Bankruptcy